Evaluation and Monitoring of Water Quantity and Quality of the Buriganga River in Bangladesh using Multi-temporal Landsat Images (The Dhaka University Journal of Earth and Environmental Sciences, 2020)
Buriganga River, the study area, is one of the most polluted and decreasing expeditiously its area in Bangladesh due to rapid urbanization, effluents of industries and factories surrounding the river, sewage disposal from Dhaka City and some anthropogenic activities. The objective of this study is to evaluate and monitor the water quantity and quality of the river using satellite remote sensing techniques. Unsupervised and indices based classification were used to derive and monitor landuse-landcover (LULC), surface water distribution (SWD), land surface temperature(LST) and total suspended material (TSM) using four sets of Landsat TM/ETM+/OLI/TIRS images of the study area from 1989 to 2015. The indices are Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI). LULC classification results showed that the water bodies and vegetation decreased and consequently urban as well bared area increased from 1989 to 2015. Results of indices (NDVI and NDWI) analysis are similar to that of unsupervised LULC outputs, that is, the water bodies decreased with increasing urban structures of the study area. The surface water distribution monitoring results from the suitable change detection GIS model indicate that the water bodies have decreased about 31.07% and accretion rate increased rapidly from 1989 to 2015 along the river bank due to urbanization and accretion activity is more prominent in north, northeast, northwest, south, southeast and eastern part. The study also shows that the rate of TSM is sporadically increasing during the study period i.e., the maximum and minimum value of TSM was 56215.53 and 1956 mg/l in 1989 and 14188714.35 mg/l and 333942 mg/l in 2015 respectively; this indicates that the water is harmful for aquatic life. Both the analyzed satellite image outcome and in situ observations reveal that land surface temperature is also increased in some part of the study area. The study results could be used to make policy for upgrading the water quality and to maintain the extent and water quantity for agriculture, navigation and fisheries sectors of the Buriganga River.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 8(1), 2019, P 61-69